Online Review Impact on Online Travel Agent toward Room Purchase Intention - Ni Made Riani Puspasari; I Wayan Jata; Nyoman Gede Mas Wiartha; Ni Desak Made Santi Diwyarthi (Westscience Press, 2025)
The advancement of information technology has reshaped consumer behavior in the tourism and hospitality sectors, particularly in hotel selection. Online reviews on Online Travel Agency (OTA) platforms have become critical sources of information, influencing purchase decisions. This study investigates the effect of online reviews on hotel room purchase intentions in Bali. Using a quantitative approach, data were collected from 100 purposively sampled respondents who had not previously stayed in Bali hotels but intended to book. Online reviews were measured across three dimensions: credibility, expertise, and pleasantness, while purchase intention was assessed through stimulation, awareness, and information-seeking. Results from descriptive and inferential analyses, including simple linear regression, show that online reviews have a positive and significant impact on purchase intentions. Online reviews explain 37.5% of the variance in purchase intention, indicating their substantial influence, while 62.5% of variance is attributed to other factors. Findings suggest that credible and informative reviews enhance consumer trust and booking likelihood. Hotels are recommended to actively encourage positive reviews, respond professionally to feedback, and leverage review insights to improve service quality and digital marketing effectiveness.